Independent prognostic value of functional mitral regurgitation in patients with heart failure. A quantitative analysis of 1256 patients with ischaemic and non-ischaemic dilated cardiomyopathy. Issue 20 (31st July 2011) - Rossi, Andrea; Dini, Frank L; Faggiano, Pompilio; Agricola, Eustachio; Cicoira, Mariantonietta; Frattini, Silvia; Simioniuc, Anca; Gullace, Mariangela; Ghio, Stefano; Enriquez-Sarano, Maurice; Temporelli, Pier Luigi
Abstract : Background: Functional mitral regurgitation (FMR) is a common finding in patients with heart failure (HF), but its effect on outcome is still uncertain, mainly because in previous studies sample sizes were relatively small and semiquantitative methods for FMR grading were used. Objective: To evaluate the prognostic value of FMR in patients with HF. Methods and results: Patients with HF due to ischaemic and non-ischaemic dilated cardiomyopathy (DCM) were retrospectively recruited. The clinical end point was a composite of all-cause mortality and hospitalisation for worsening HF. FMR was quantitatively determined by measuring vena contracta (VC) or effective regurgitant orifice (ERO) or regurgitant volume (RV). Severe FMR was defined as ERO >0.2 cm 2 or RV >30 ml or VC >0.4 cm. Restrictive mitral filling pattern (RMP) was defined as E-wave deceleration time <140 ms. The study population comprised 1256 patients (mean age 67±11; 78% male) with HF due to DCM: 27% had no FMR, 49% mild to moderate FMR and 24% severe FMR. There was a powerful association between severe FMR and prognosis (HR=2.0, 95% CI 1.5 to 2.6; p<0.0001) after adjustment of left ventricular ejection fraction and RMP. The independent association of severe FMR with prognosis was confirmed in patients with ischaemic DCM (HR=2.0, 95% CI 1.4 to 2.7; p<0.0001) and non-ischaemic DCM (HR=1.9, 95% CI 1.3 to 2.9; p=0.002). Conclusion: In a large patient population it was shown that a quantitatively defined FMR was strongly associated with the outcome of patients with HF, independently of LV function.